ANALISIS HUKUM PERLINDUNGAN HAK PATEN DALAM ERA DIGITAL: STUDI KASUS PENGGUNAAN TEKNOLOGI BLOCKCHAIN - Arief, Anggreany; Putri, Andi Istiana Inayah Dwi; Gazali, Indrahayu Umar; Asmah, Asmah (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The digital era has driven significant transformation in intellectual property rights protection, including patent rights. The emergence of blockchain technology with its characteristics of decentralization, immutability, and transparency offers new opportunities to strengthen patent rights protection, but also raises legal challenges related to validity, jurisdiction, and data privacy. This study aims to analyze the legal consequences of patent infringement in the digital era and examine the potential application of blockchain technology in the patent protection system in Indonesia. The method used is normative juridical with a legislative approach and qualitative analysis of primary and secondary legal materials. The results of the study show that blockchain has great potential in creating a more efficient and transparent patent protection mechanism, but its implementation requires legal reform and recognition of digital evidence. This study emphasizes the need for an adaptive and integrative legal framework so that patent protection in Indonesia can be responsive to developments in digital technology